Comparison of a TaqMan-based real-time polymerase chain reaction with conventional tests for the detection of Trichomonas vaginalis. Issue 2 (7th November 2006) - Pillay, A; Radebe, F; Fehler, G; Htun, Y; Ballard, R C
Abstract : Objective: To compare a TaqMan-based real-time polymerase chain reaction (PCR) with conventional PCR, culture, and wet-mount microscopy for the diagnosis of trichomoniasis in women. Methods: Vaginal swabs from 119 women were tested for Trichomonas vaginalis by wet mount and culture. Paired vaginal lavage and urine specimens were tested by conventional and real-time PCR. Results: Using an expanded "gold standard", defined as a positive culture result using vaginal swabs and/or a positive PCR test using TVK3/7 primers, the overall prevalence of T vaginalis in the study population was 65.5% (78/119). The detection rate of T vaginalis was 65.5% (78/119) and 36.9% (44/119) by conventional PCR using vaginal washings and urine specimens, respectively; 68.9% (82/119) by real-time PCR using vaginal washings and 61.3% (73/119) by real-time PCR using urine specimens. The sensitivities of conventional PCR using vaginal washings and urine and real-time PCR using vaginal washings and urine, compared with the gold standard were 100%, 56.4%, 100% and 76.7%, and the specificities of these tests were 100%, 97.6%, 82.9% and 97%, respectively. Conclusions: The real-time PCR test proved to be significantly more sensitive than culture and wet-mount microscopy, although its specificity was slightly lower than these tests. In addition, it was more sensitive, rapid and less time consuming than conventional PCR for the detection of T vaginalis .